The COVID‐19 vaccine: Attitudes and vaccination in patients with autoimmune inflammatory rheumatic diseases. Issue 2 (15th February 2022) - Chen, Jiali; Cai, Wenxin; Liu, Tian; Zhou, Yunshan; Jin, Yuebo; Yang, Yue; Chen, Shi; Tang, Kun; Li, Chun
Abstract: Background: We examined attitudes toward the COVID‐19 vaccine, potential factors underlying these attitudes, and ways to increase vaccination willingness in autoimmune inflammatory rheumatic diseases (AIIRD) patients. Methods: A multicenter, web‐based, observational survey using an online questionnaire was conducted among AIIRD patients aged ≥18 years from May 24, 2021, to June 3, 2021. Participants were 3104 AIIRD patients (2921 unvaccinated and 183 vaccinated). Results: Of the unvaccinated patients, 32.9% were willing to receive the COVID‐19 vaccine, 45.0% were uncertain, and 14.8% were unwilling. When vaccination was recommended by physicians, patients' willingness increased to 93.8%. Participants' main concerns were that the vaccine may aggravate AIIRD disease (63.0%) and may cause vaccine‐related adverse events (19.9%). Female patients were less likely to be vaccinated. However, patients who had children aged ≤18 years were more willing to be vaccinated. In addition, vaccination willingness was higher in patients with trust in the safety and efficacy of the COVID‐19 vaccine. Notably, 183 (5.9%) patients were vaccinated. The major vaccination side effects were injection reaction, myalgia, and fatigue. At a median follow‐up of 88 (38, 131) days, patients' disease activities were stable. Conclusions: The findings show that AIIRD patients were unwilling to receive the COVID‐19 vaccine because of fears of potential disease exacerbation and additional adverse events. Sociodemographic characteristics and concerns about COVID‐19 disease and vaccines had a significant effect on vaccination willingness. Key points: The percentage of patients willing to receive the COVID‐19 vaccine greatly increased when vaccination was recommended by a physician. Gender, marital status, age of the patients' children, smoking, trust in the safety and efficacy of the vaccine, and previous vaccinations had significant effects on the willingness of patients with AIIRDs to receive the COVID‐19 vaccine. The data from vaccinated patients indicated no aggravation of AIIRD or additional adverse events. Abstract : The population characteristics of AIIRD patients with different attitudes towards COVID‐19 vaccine.